2001
DOI: 10.1590/s0102-311x2001000100023
|View full text |Cite
|
Sign up to set email alerts
|

Freqüência horária e sazonalidade de Lutzomyia longipalpis (Diptera: Psychodidae: Phlebotominae) na Ilha de São Luís, Maranhão, Brasil

Abstract: This article presents the hourly and seasonal distribution of the Lutzomyia longipalpis sand fly captured on São Luís Island, Maranhão State. A total of 11,200 specimens were captured during monthly use of CDC light traps indoors and in animal sheds, between 6:00 PM and 6:00 AM, in 1996 and 1997. The sand fly behaved as an annual species, with a high frequency year-round, while it was most abundant during the rainy season (57.2%) as compared to the dry season (42.8%). The highest frequencies during the rainy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 11 publications
(11 reference statements)
5
17
0
13
Order By: Relevance
“…This association was reported by Rebêlo (2001a) for the municipality of Buriticupu (state of Maranhão) where high densities of L. whitmani were coincident with increasing ACL human cases. In the present work, a similar analysis provided information on the same trend, i.e, increasing numbers of ACL human cases just after higher population densities of insect vectors ( Figs 3, 4).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This association was reported by Rebêlo (2001a) for the municipality of Buriticupu (state of Maranhão) where high densities of L. whitmani were coincident with increasing ACL human cases. In the present work, a similar analysis provided information on the same trend, i.e, increasing numbers of ACL human cases just after higher population densities of insect vectors ( Figs 3, 4).…”
Section: Discussionsupporting
confidence: 56%
“…In Porterinha (north of the state of Minas Gerais), frequency of precipitation showed to affect directly the amount of phlebotomine collected in the region (Barata et al 2004). Rebêlo (2001a) have showed that there was a high frequency of L. longipalpis during the whole year in São Luis Island, with an increasing trend in rainy periods when compared to the dry periods. Temperature, humidity, and precipitation showed no influence in monthly insect density.…”
Section: Discussionmentioning
confidence: 99%
“…Add to this social crises and environmental changes such as prolonged and periodical droughts enabling new VL foci in urban areas (Vieira & Coelho 1998). The non-significant correlation between insect density and the bioclimatic variables under study had also not been observed by Souza et al (2004) in Belo Horizonte, and Rebêlo (2001) in São Luis, state of Maranhão. The non-significant effect of temperature on phlebotomine density was reported by Barata et al (2004), although Monteiro et al (2005) have found correlations between high temperatures and peaks of VL transmission.…”
Section: Discussionmentioning
confidence: 59%
“…In Venezuela the greatest activity of this species was recorded before 23.00h 15 , and in Maranhão, Brazil, in animal sheds Lu. longipalpis was mainly collected between 18.00h and 20.00h 29 . These results highlight the risk associated with the nocturnal habits of the people of Posadas, who usually remain in their backyards during the summer months from dinnertime to around midnight.…”
Section: Discussionmentioning
confidence: 99%